Business Takeover or New Venture? Individual and Environmental Determinants From a Cross‐Country Study. (5th June 2012) - Block, Joern; Thurik, Roy; van der Zwan, Peter; Walter, Sascha
Abstract : Whereas the determinants of entrepreneurial choice have been thoroughly analyzed in the literature, little is known about the preferred mode of entry into entrepreneurship, such as taking over an existing business or starting a new venture. Using a large international data set, this study reports considerable differences in takeover preferences across 33 countries. Hierarchical (multilevel) regressions are performed to explore individual‐level and country‐level determinants of the preferred mode of entry. At the individual level, a person's human capital, risk attitude, and inventiveness influence the preference for starting a new venture versus taking over an existing business. At the country level, the culture‐inherent level of risk tolerance, the country's level of innovation output, and the administrative difficulty of starting a new business are found to explain the between‐country variation in the preferred mode of entry. Implications of our findings for research and practice are also discussed.